WAQF BOARD AS NAZHIR: WAQF LAND MANAGEMENT IN ISLAMIC BOARDING SCHOOLS (WAKAF LEGAL STUDY NO. 41 OF 2004) - Faisal Khalid; Hafsah Hafsah; Mhd Yadi Harahap (Proceeding International Seminar of Islamic Studies, 2023)
This study focuses on the implementation of Waqf land management in Ar-Raudlatul Hasanah Islamic boarding schools under Waqf Law No. 41 of 2004. According to statistics from the Ministry of Religious Affairs, Waqf's potential is huge, so study it, but the problem lies in the professionalism of management and management. Nazir's presence is embarrassing, but the Four Mindset is not weakened as a condition. This study uses legal empirical methodology addressed through a field approach in the form of case studies. The data obtained illustrate the positioning of waqf institutions in Islamic boarding schools like Nazir, how waqf governments manage and develop waqf assets, and the problems and challenges facing institutions. face to face. gain. As a further consideration, it should be noted that the form of management of waqf assets as stipulated in Law No. 41 of the Republic of Indonesia of 2004 may be the legal basis for the adjustment and use of waqf assets for livelihood needs. Nationality is very important. The Waqf Regulator continues to pay close attention to Waqf's administration, licensing, and fundraising activities, and staff training. Therefore, waqf training should be developed at the same time as waqf training.